Diagnosis of deep vein thrombosis using autologous indium-III-labelled platelets. Issue 6269 (28th March 1981) - Fenech, A; Hussey, J K; Smith, F W; Dendy, P P; Bennett, B; Douglas, A S
Abstract : Forty-eight patients who had undergone surgical reduction of a fractured neck of femur or in whom deep vein thrombosis was suspected clinically were studied by ascending phlebography and imaging after injection of autologous indium-111-labelled platelets to assess the accuracy and value of the radioisotopic technique in diagnosing deep vein thrombosis. Imaging was performed with a wide-field gammacamera linked with data display facilities. Phlebography showed thrombi in 26 out of 54 limbs examined and a thrombus in the inferior vena cava of one patient; imaging the labelled platelets showed the thrombi in 24 of the 26 limbs and the thrombus in the inferior vena cava. The accumulation of indium-111 at sites corresponding to those at which venous thrombi have been shown phlebographically indicates that this radioisotopic technique is a useful addition to methods already available for the detection of deep vein thrombosis.